Analysis of Auto Release Seatbelt System for Multipurpose Vehicle - Ahmad, Mohamad Khairi; Mahmudin, Rahmah; Mohamed, Norirda; Darlis, Nofrizalidris; Zainal Abidin, Shaiful Fadzil; Mohamed Nazar, Mohamed Ihsan Sabri (Journal of Automotive Powertrain and Transportation Technology, 2023)
An automatic seat belt release system is provided for installation in conjunction with the vehicle’s seat belt system. In the event that the vehicle sustains an impact of sufficient magnitude to necessitate the emergency release of the seat belt system, an electrically operated actuator located near the seat belt is actuated to release the seat belt system after 5 seconds time interval. The aim of this study is to design and develop coding language for Auto Release Seatbelt System. The system for Auto Release Seatbelt is installed inside the passenger cabin and the release mechanism fixed at the seatbelt buckle. The system is tested after the installation on a multipurpose vehicle (MPV). The 12V cigarette lighter socket is used to power the system. A crash collision impact sensor, an accelerometer, a gyroscope, a developer board, and a solenoid actuator comprise in the designed emergency release system. The crash collision impact sensor identifies when the vehicle collides, and the gyroscope sensor determines the vehicle’s orientation after the impact, if the gyroscope detects no change in orientation, it triggers the development board’s preset timer. The solenoid is activated to press the custom release mechanism that will remove the seat belt once the specified time period has passed.